Transformasi Teknologi: Peningkatan Kemampuan Siswa SD Islam Saroja melalui Pelatihan Google Docs - Lemantara, Julianto; Syahputra, Noval Azmi; Hadi, Arysatya; Gadi, Muhammad Axelle Mahrus; Lianata, Dave; Ramadhan, Aditya (LPPM Universitas HKBP Nommensen, 2024)
SD Islam Saroja faces real challenges in the form of limitations in learning tools. The main issue identified is the lack of understanding and application of Google Docs among students at SD Islam Saroja. This research aims to analyze the impact of Google Docs training on students' level of understanding at Saroja Islamic Elementary School. The research method was carried out using a quantitative and qualitative approach and the training was carried out over two days. The research results showed 94.7% agreed that the room used was clean, tidy and supported the implementation of activities. Apart from that, 92.1% of students agreed that the presenters were communicative, interactive and fun in delivering the material. The presenters were also considered to have a sense of empathy because they understood the students' condition when they were bored. The most positive research results were 94.7% of students felt the material was easy to understand and suited their needs. In addition, 92.1% of students rated this training material very useful.Top of Form